2006
DOI: 10.1007/s00221-006-0636-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of unilateral vestibular deafferentation on the initial human vestibulo-ocular reflex to surge translation

Abstract: Transient whole-body surge (fore-aft) translation at 0.5 G peak acceleration was administered to six subjects with unilateral vestibular deafferentation (UVD), and eight age-matched controls. Subjects viewed eccentric targets to determine if linear vestibulo-ocular reflex (LVOR) asymmetry might lateralize otolith deficits. Eye rotation was measured using magnetic search coils. Immediately before surge, subjects viewed a luminous target 50 cm away, centered or displaced 10° horizontally or vertically. The targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 77 publications
(92 reference statements)
0
5
2
Order By: Relevance
“…The small and symmetric magnitude of the LVOR deficit in UVD has made it difficult to lateralize otolith pathology based on test findings. Exceptions have involved the anteroposterior otolith VOR with an eccentric visual target in monkey UVD (Angelaki et al 2000) and human UVD (Tian et al 2006). However, in contrast to the modest otolith VOR deficits during pure linear acceleration, the current study found that the otolith VOR evoked by eccentric yaw rotation with near target viewing was profoundly and asymmetrically ablated during ipsilesional rotation at high acceleration.…”
Section: Profound Deficit and Absence Of Recovery Of Transient Otolitcontrasting
confidence: 88%
See 2 more Smart Citations
“…The small and symmetric magnitude of the LVOR deficit in UVD has made it difficult to lateralize otolith pathology based on test findings. Exceptions have involved the anteroposterior otolith VOR with an eccentric visual target in monkey UVD (Angelaki et al 2000) and human UVD (Tian et al 2006). However, in contrast to the modest otolith VOR deficits during pure linear acceleration, the current study found that the otolith VOR evoked by eccentric yaw rotation with near target viewing was profoundly and asymmetrically ablated during ipsilesional rotation at high acceleration.…”
Section: Profound Deficit and Absence Of Recovery Of Transient Otolitcontrasting
confidence: 88%
“…Testing of the VOR during pure translation appears insufficiently robust to be a practical lateralizing test of otolith function (Tian et al 2006). However, high acceleration eccentric yaw rotation with a near target in the current study disclosed a profound, immediate, enduring and lateralizing deficit in the otolith VOR in UVD.…”
Section: Potential As Clinical Test For Otolith Pathologycontrasting
confidence: 71%
See 1 more Smart Citation
“…However, these asymmetries reduce over time such that long term patients (6-10 weeks) show no consistent asymmetry to rolltilt stimuli (7). Similarly, patients 6 weeks after surgery show no asymmetry for linear lateral translations (81,107). This is in sharp contrast to the semicircular canal system where response asymmetries after unilateral loss are permanent as shown by the head impulse test (108)(109)(110).…”
Section: Discussionmentioning
confidence: 98%
“…This horizontal eye movement to lateral linear acceleration (80) has been used to try to identify the unilateral utricular loss, by analogy with the success of the horizontal eye movement to angular acceleration identifying the side of unilateral semicircular canal loss (81). A horizontal angular acceleration toward the affected ear results in a reduced horizontal compensatory eye velocity response and so permanently identifies the affected semicircular canal (82).…”
Section: Oculomotor Response To Linear Translationmentioning
confidence: 99%